Pengaruh Kesiapan Pegawai Menuju Numerasi Terhadap Kinerja Aparatur Sipil Negara Di Polda Jawa Tengah - Ibnu Khajar; Lutfi Nurkolis; H Sri Hartono; Agustina Fitrianingtum (Publikasi Indonesia, 2025)
The purpose of this research is to determine: 1) the influence of awards on the performance of State Civil Servants at the Central Java Regional Police, 2) the influence of work discipline on the performance of State Civil Servants at the Central Java Regional Police, 3) the influence of individual behavior on the performance of State Civil Servants at the Central Java Regional Police , and 4) the influence of rewards, work discipline, and individual behavior on the performance of the State Civil Apparatus at the Central Java Regional Police. This type of research is quantitative research. The population in this study was all Central Java Regional Police ASN, totaling 1,375 people, with a sample of 279 people. The sampling technique was proportional random sampling. The data collection technique used was a questionnaire. The data analysis used is descriptive analysis, prerequisite tests, and hypothesis testing which includes single linear regression analysis and multiple linear regression. To analyze the data, SPSS for Window Release 28 program facilities were used. The results of the research show that: 1) awards have a positive and significant influence on the performance of the State Civil Apparatus at the Central Java Regional Police, 2) work discipline has a positive and significant influence on the performance of the State Civil Apparatus at the Central Java Regional Police, 3) individual behavior has a positive and significant impact on the performance of the State Civil Apparatus at the Central Java Regional Police, and 4) rewards, work discipline and individual behavior have a positive and significant influence on the performance of the State Civil Apparatus at the Central Java Regional Police